Abdominolabial hydrocele of the canal of Nuck: A rare entity (Indian Journal of Case Reports, 2019)
Hydrocele of the canal of Nuck also called the “female hydrocele” is a rare entity in females. The processus vaginalis peritonei is a tubular fold of peritoneum that invaginates into the inguinal canal along with the round ligament. It usually gets obliterated by birth or during early infancy, but if this communication remains patent, it may lead to the development of an indirect inguinal hernia or hydrocele. Here, we present the case of a 32-year-old female who complained of swelling in the right inguinal region. Contrast-enhanced computed tomography scan of abdomen and pelvis was suggestive of a cystic lesion in the right inguinal region which was seen extending from mons pubis up to the right iliac fossa in the retroperitoneum likely suggestive of hydrocele of the canal of Nuck. Surgical excision of the cyst was done.